2007
DOI: 10.1212/01.wnl.0000257816.92101.54
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical inhibition of the motor cortex in Segawa disease (DYT5)

Abstract: Normal SICI of the motor cortex in Segawa disease stands in remarkable contrast to the previously reported reduction of SICI in focal dystonia. This suggests that the gamma-aminobutyric acid A system of the motor cortex is intact in Segawa disease. The pathophysiologic mechanisms for dystonia must be partly different between Segawa disease and focal dystonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Both SICI and ICF were normal in our patients, similar to a previous study and did not change after l ‐dopa intake. In contrast, in another study, abnormally reduced SICI at baseline could be normalized after dopaminergic treatment .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both SICI and ICF were normal in our patients, similar to a previous study and did not change after l ‐dopa intake. In contrast, in another study, abnormally reduced SICI at baseline could be normalized after dopaminergic treatment .…”
Section: Discussionsupporting
confidence: 91%
“…An increased facilitatory drive in dorsal premotor (PMd) to primary motor cortex (M1) connections has been demonstrated in Parkinson patients, whereas inhibitory influences seem to be up‐regulated in these circuits in dystonia . Although M1 excitability has been studied in DRD PMd‐M1 circuit activity is unclear in these patients. To this end, we measured these circuits in DRD, using a transcranial magnetic stimulation (TMS) dual‐pulse conditioning paradigm that has previously been useful to depict abnormal PMd‐M1 network activity in parkinsonism and dystonia .…”
mentioning
confidence: 99%
“…The same group also pointed out that because SICI selectively targets late I waves, it is difficult to interpret measurement of SICI in different patient populations (Hanajima & Ugawa, ; Hanajima et al . , ). If SICI is reduced, is it because the GABAergic circuits are less excitable, or is it because the test pulse recruits proportionately more early than late I waves or more D than I waves (Hanajima et al .…”
Section: Introductionmentioning
confidence: 99%
“…Research in focal dystonia suggests that the impaired cortical inhibition is due to primary basal ganglia dysfunction. However, recent studies applying TMS in dopa-responsive dystonia [5] and myoclonus-dystonia (M-D) patients [6] did not fi nd evidence of abnormalities of motor cortical inhibition or facilitation, suggesting that the γ-aminobutyric acid A system is intact. One study using TMS in a small group of patients with DYT11 M-D reported neurophysiologic fi ndings suggestive of a brainstem origin [7].…”
Section: Pathophysiologymentioning
confidence: 97%